Study on galvanic corrosion caused by coating failure in heat exchangers for chemical cooling water systems - Zuo, Zeyu; Yu, Zhenhua; Hou, Qingle; Ren, Kai; Zhang, Jie; Zhang, Chengjun; Zhang, Ruiyong; Sand, Wolfgang; Hu, Zhao; Chen, Xilei; Duan, Jizhou; Hou, Baorong (Frontiers in Materials, 2025)
Cooling water heat exchangers are essential components in chemical production processes, requiring long-term stability under corrosive circulating cooling water conditions. Coating protection technology has become increasingly widespread for mitigating corrosion in these systems. However, prolonged immersion in cooling water during operation can result in coating degradation and detachment. This study examines the corrosion behavior associated with coating damage in cooling water heat exchangers under varying immersion times. Coated carbon steel specimens were coupled with artificially stripped specimens to simulate large cathode and small anode systems in a cooling water environment. The results reveal that the corrosion rate of the small exposed anode increases as the exposure area decreases. Simultaneously, the adhesion between the coating and the substrate of the large cathode weakens with immersion time, leading to the formation of voids regardless of the exposure area. The findings indicate that in practical applications, smaller areas of coating delamination drive localized corrosion at the exposed substrate, whereas larger areas promote internal corrosion beneath the coating, ultimately leading to complete coating failure.